2021
DOI: 10.1111/1462-2920.15396
|View full text |Cite
|
Sign up to set email alerts
|

Candidatus Sarmatiella mevalonica’ endosymbiont of the ciliate Paramecium provides insights on evolutionary plasticity among Rickettsiales

Abstract: Members of the bacterial order Rickettsiales are obligatorily associated with a wide range of eukaryotic hosts. Their evolutionary trajectories, in particular concerning the origin of shared or differential traits among distant sub-lineages, are still poorly understood. Here, we characterized a novel Rickettsiales bacterium associated with the ciliate Paramecium tredecaurelia and phylogenetically related to the Rickettsia genus. Its genome encodes significant lineage-specific features, chiefly the mevalonate p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 109 publications
(230 reference statements)
5
16
0
Order By: Relevance
“…Nesciobacter’, possibly representing an evolutionary shared trait. Interestingly, multiple and likely convergent truncations were found among Rickettsiales (Castelli et al ., 2021), including in several bacteria associated with Paramecium , perhaps indicating some host‐dependent role for such condition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nesciobacter’, possibly representing an evolutionary shared trait. Interestingly, multiple and likely convergent truncations were found among Rickettsiales (Castelli et al ., 2021), including in several bacteria associated with Paramecium , perhaps indicating some host‐dependent role for such condition.…”
Section: Resultsmentioning
confidence: 99%
“…Phylogenomic analyses were performed on single copy orthologs (75 genes, 12 996 total positions), extracted from a dataset including Gromoviella agglomerans , all the 15 Holosporales bacteria with published (December 2020) genome assemblies (excluding metagenome‐assembled ones), plus six other Alphaproteobacteria as outgroup (details in the Supporting Information text S2). ML and BI trees were then inferred as described previously (Castelli et al ., 2021).…”
Section: Methodsmentioning
confidence: 99%
“…The Rickettsiales symbionts of protists infect diverse host groups including amoebae ( Schulz et al 2016 ), ciliates ( Floriano et al 2018 ), algae ( Yurchenko et al 2018 ), and various flagellates ( George et al 2020 ). Phage-related genes are reported from several Rickettsiales endosymbionts of protists ( Floriano et al 2018 ; Castelli et al 2019 , 2021 ), and are also found in another endosymbiotic group of Alphaproteobacteria called Holosporaceae ( Garushyants et al 2018 ; Midha et al 2021 ; Castelli et al 2022 ). Holosporaceae is a subgroup of the order Rhodospirillales ( Muñoz-Gómez et al 2019 ), and is also made up of obligate endosymbionts that infect diverse eukaryotes including animals ( Nunan et al 2013 ), amoebae ( Schulz et al 2014 ), ciliates ( Dohra et al 2014 ; Castelli et al 2022 ), rhizarians ( Muñoz-Gómez et al 2019 ), and a variety of flagellates ( George et al 2020 ; Midha et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of bacteria species reside as endosymbionts in both microeukaryotes, and algae [1][2][3][4][5][6][7][8]. Symbiont presence can affect the biology of their host in significant ways, from reproductive manipulation [9,10] to stress tolerance [11], nutrient production [12,13] and methanogenesis [14].…”
Section: Introductionmentioning
confidence: 99%